Understanding Child Sexual Abuse in the Religious Contexts in Indonesia through a Lived Experience - Alyssa Putri (Salasika, 2022)
Child sexual abuse in Indonesia occurs in various settings, including home, school, or work (in places where child labor is common). The National Commission for Child Protection (Komnas Perlindungan Anak) stated that52% of cases of violence against children from 2020 to mid-2021 were sexual violence (Suminar, 2021).The increasing number of child abuse cases encourages parents to send their children to religion-based schools that, they think, offer safer environments. Based on the data collected by KOMNAS Perempuan, 19% of sexual violence occurred in Islamic boarding schools or Islamic-based education and 3% in Christian-based education. KPAI also noted that 88% of perpetrators of sexual violence in schools were teachers, mostly religion teachers (13.3%) and physical education teachers (40%), the rest being computer, arts, social studies, Indonesian, or other teachers, while 22% were principals. The objective of the study is to unravel the experience in a religious setting. The finding narrated that the effects of child sexual abuse could include depression, post-traumatic stress disorder, anxiety, complex post-traumatic stress disorder, and physical injury to the child, among other problems. In addition, there was no support from the school community for the victim of child abuse.